Programmed instruction on the present perfect tense for grade six - Santiago, Apolonia Bermudez 1920- (s.n.], 1972)
This paper presented a self-instructional material. It is based on the goals or objectives in the use of English present perfect tense expected of a Grade Six pupil in Philippine public schools.